(untitled) (Proceedings of the YSU B: Chemical and Biological Sciences, 2002)
The mycological investigation of the defeat tuber of potatoes, showed the caused agents of disease considered to be widely spread rhizosphere and rhizoplane researched cultures, including these species of genus’s: Alternaria, Fusarium, Rhezoctonia, Cladosporium, Oospora. The disease of tuber is caused not by separated species, but association of fungi.